The Effectiveness of the Problem-Based Learning Model to Enhance Students' Critical Thinking Skills on Conservation Biology Courses - Iwan; Sutiman Bambang Sumitro; Ibrohim; Fatchur Rohman (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study is to ascertain how the problem-based learning approach affects students' critical thinking abilities in courses on conservation biology. This study design uses a non-equivalent control group in a quasi-experiment. Essay exam questions totaling 10 valid and reliable numbers served as the study's instrument. Pre-test and post-test questions were used to gather data. Descriptive statistics and inferential statistical tests, namely the covariance (ANCOVA) analysis with pretest values as variables at a significance level of 0.05%, were used to evaluate the research data. The IMB 23 SPSS program was utilized for data analysis because the data were homogeneous and regularly distributed. The findings demonstrated that, with a significance value of 0.000 < 0.05, there was a significant difference in the critical thinking abilities of students taught using the conventional model and those taught using the problem-based learning model. The conclusion is that in conservation biology classes, the problem-based learning approach helps students develop their critical thinking skills.